Impact of remote work on Portuguese software professionals during the COVID-19 pandemic - Almeida, Ana J.; Cunha, Jácome; Fernandes, João M. (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2023: Anais do XXVI Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2023.24703, 2023)
Although remote work was already possible and used in some contexts, the COVID-19 pandemic made it normal and, in some situations, even mandatory. This was the case in Portugal and in particular in its software industry. Given this abrupt change in how we work, it became pressing to investigate the impacts of this profound change to remote work, so that we can cope with the potential negative consequences (professional, personal, etc.). Thus, the goal of this work is to study the impact of the referred change to remote work, due to the COVID-19 pandemic, on software professionals in Portugal. To achieve this goal, a survey was prepared and distributed via email, LinkedIn, and Instagram. In total, 176 valid answers were collected from software professionals working in Portugal from 38 different companies. After the performed statistical analysis on the targeted population and focusing on the 10 elaborated research questions, two major findings can be concluded with certainty: (i) having worked in a remote regime before the pandemic period has a strong relationship with a higher frequency of use of teleconference tools after this period, and (ii) participants who do not feel safe about coming back to a fully on-site regime are more likely to prefer a fully remote regime than the ones who feel safe, while the latter group is more likely to prefer a hybrid regime.